Enforcing Sustainable Forest Management Policies: An Assessment of the Institutional Structures for VPA Implementation in Ghana - Sarfo-Adu, Gordon Kofi (Environmental Management and Sustainable Development, 2021)
Public policy formulation in the forestry management space is an essential step in addressing issues of environmental degradation. That notwithstanding, policies will remain mere intents if they are not forged with appropriate structures and institutional underpinnings. This study assesses the institutional and structural mechanisms adopted to foster effective implementation of the Voluntary Partnership Agreement in Ghana. The qualitative case study design was employed to gather data from purposively selected respondents. The study observes that after ratification of the VPA in Ghana, this was forged with subsequent measures to ensure smooth operationalization of same. The structures include a Legality Assurance System (LAS); chain of custody and wood tracking system (GWTS); establishment of a Timber Verification Department to check and verify the legality of all timbers among others. The structures also entail collaborative governance, transparency and accountability measures to ensure operationalization of the VPA requirements. The study observes that where there are multiple, overlapping and independent actors along the value chain, trust and credibility is built such that those in the downstream of the implementation remain very careful and conscientious in their operations and dealings. The study concludes that relevant implementation structures interspersed with actor constellations, and multi-stake holding remain cornerstone of SFM arrangements.